IFRS Higher Technology Courses - Porto Alegre: management models in/of Higher Education - Julian Silveira Diogo de Ávila Fontoura (Universidade Federal do Oeste da Bahia, 2020)
The investigation presented here aims to indicate possible institutional arrangements present in the context of Higher Education articulated the modality of Professional, Scientific and Technological Education in the context of the Federal Institute of Education, Science and Technology of Rio Grande do Sul - Porto Alegre, from the models of management implemented in the Higher Technology Courses of the institution, from the perspective of the course coordinators. Depending on the nature of the study, we used the qualitative, descriptive-exploratory approach, aligned with the theoretical-methodological perspective of the Policy Cycle Approach and the Multidimensional Paradigm of Education Administration. The results of the study point to the complexity in which Higher Education Management is inserted in the context of the institution, where the management model is presented in a way that incorporates the notions of economic efficiency, pedagogical effectiveness, cultural relevance and political effectiveness in its practices everyday life.